Determinants of Students’ Participation in Campus Organizations and School Management Functions in Selected Higher Educational Institutions - Adil, Jimmy Jiamah V. (JPAIR Multidisciplinary Research, 2009)
Student organizations afford rich learning experiences outside the classroom. Furthermore, they perform indispensable functions in fulfilling the school’s philosophy, mission, and vision. This study looked into the factors that determined students’ participation in campus organizations and involvement in school management functions. The respondents were 312 student leaders in 14 tertiary schools in Regions X, XI and ARMM. The data were gathered through researcher-made questionnaires, then analyzed using Chi-square, Pearson r, T-test and F-test. The key findings were: among the motivations for students’ participation in organizations, learning/ experience and authority/recognition appeared highly important. The school administrators’ dealing styles supportive/responsive and consultative/participative had higher mean scores. Significant correlations between the administrators’ dealing styles and the student leaders’ participation in campus organizations and involvement in school management functions were confirmed.